A Portrait of Family Support During Treatment Patients with Coronary Heart Disease - Wahyuningsih, Indah Sri (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2021)
Family support in patients with coronary heart disease is an important role during treatment. Support from the family has a positive impact on patient adherence to treatment and improves the patient's quality of life. This study aims to determine the portrait of family support during the treatment of patients with coronary heart disease. This type of research uses a quantitative descriptive design involving 192 coronary heart disease patients who were selected based on a purposive sampling technique with inclusion criteria, namely outpatients, having a partner or family member who lives in the same house, willing to be research respondents, not experiencing verbal communication disorders. The family support assessment sheet used a family support questionnaire developed by the researcher. The results showed that the majority of the patient's family support in the adequate category was 64.6%, good family support was 26.1% and the family support was lacking was 9.3%. The conclusion of this study is that good family support will help the patient's healing process during treatment and can improve the quality of life of patients with coronary heart disease. Nurses are advised to involve the family in providing nursing interventions so that patients are obedient during treatment.